Characteristics and Glycemic Index of Corn “Kipang” added by Coconut Dregs - Refdi, Cesar Welya; Sayuti, Kesuma; Yasen, Nadia Mardiah; Fajri, Prima Yaumil (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This study aimed to investigate the impact of incorporating coconut dregs on the characteristics of corn kipang, identify the optimal addition level based on organoleptic and chemical tests, and determine the glycemic index of kipang products with coconut dreg additions. The research design was completely randomized (CRD) with six treatments and three replications. The treatments given in this study were A (0%), B (2% coconut dregs), C (4% coconut dregs), D (6% coconut dregs), E (8% coconut dregs), and F (10% coconut dregs). The research data were statistically analyzed using ANOVA and continued with DNMRT analysis at the 5% level. The best treatment based on chemical analysis of organoleptic tests, chemical analysis of corn kipang with the addition of coconut dregs is treatment F (addition of 15% coconut dregs) with the following average values: moisture content (8.13%), ash content (1.67 %), fat (6.90%), protein (4.04%), carbohydrates (79.27%), crude fiber (4.40%), glycemic index (56.35%) and organoleptic acceptance values with the average panelists' preference for color was 3.77 (liked), aroma 4.07 (liked), and taste 4.27 (liked), and crispness 4.10 (liked). Corn kipang products with 10% coconut dregs are classified as medium IG category (56.35), while corn kipang products without adding coconut dregs are classified as high IG category (75.31). This shows that adding coconut dregs can reduce the IG value of a product. Contribution to Sustainable Development Goals (SDGs)SDG 3: Good Health and Well-beingSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production